The Role of Consumer Perception in Mediating the Influence of Brand Communication and Brand Credibility on Brand Trust - Indira Wiyana Pramesti; Aang Curatman (International Journal Labs, 2026)
The existence of illegal cosmetics circulating in the market and has the potential to reduce consumer confidence in the cosmetics industry in Indonesia. Therefore, this study aims to measure the extent to which Brand Communication and Brand Credibility affect Brand Trust which is influenced by Consumer Perception as an intervening variable for Pink Flash cosmetic products. This study used a quantitative approach with SEM-PLS analysis techniques. Data was collected from 196 respondents aged 18-25 years in the Ciayumajakuning area. This study tested all hypotheses and obtained positive and significant results. This shows that Brand Trust based on Consumer Perception, both directly and indirectly, occurs due to the positive and significant influence of Brand Communication and Brand Credibility. Brand Credibility is the variable that has the most impact on consumer perception and trust with a value (O=0.700). Thus, the synergy between clear communication and solid trust is an important step to maintain trust in security-sensitive situations.